(untitled) (Medicine Today, 2020)
Introduction: Psoriasis is a lifelong autoimmune disease which is characterized by white to red color patches of abnormalskin with patches of itchy and scaly. The term psoriasis derived from Greek word “psora” which means “itch”. It is achronic skin disease, touching about 2% of worldwide population. Different types of psoriasis have been reported such asplaque psoriasis, psoriatic arthritis, scalp psoriasis, flexural (inverse) psoriasis, guttate psoriasis, pustular psoriasis, nailpsoriasis, erythroderma which can be diagnosed by solid conclusion such as skin biopsies etc. Case report: We present thecase of a 55-years-old male with psoriasis. The diagnosis of psoriasis is based on the clinical features and history, as wellas on histopathological examinations of patient’s tissue specimens. Any final diagnosis should include a differentialdiagnosis which includes severe seborrheic dermatitis, Contact dermatitis, pityriasisrubrapilaris and mycosis fungoideswhich can be clinically indistinguishable from a severe form of psoriasis. Histopathological studies are also generallyneeded to achieve a definitive diagnosis. After histopathological confirmation of psoriasis methotrexate therapy has beenstarted. Discussion: After comparing this case with several published articles/case reports on psoriasis we found somesimilarity regarding presentation, use and good response to methotrexate therapy but dissimilarity regarding response tosteroid therapy. Conclusion: Our patient showed an excellent response to methotrexate medication Medicine Today 2020 Vol.32(2): 145-147